The IMF-FSB Early Warning Exercise : Design and Methodological Toolkit. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Early Warning Exercise (EWE) draws together a combination of analytical techniques, practical experience, seasoned judgment and unique databases in order to assess the potential consequences associated with economic and financial tail risks. There are several key features of the exercise. First, the exercise aims to help prevent the occurrence of financial crises and to limit their potential damage, not to predict the timing of crises. Second, coverage is fairly comprehensive, including both advanced and emerging economies. Third, the EWE is based on rigorous analysis and cutting-edge techniques, but it uses a holistic approach, drawing also various other tools rather than relying on a single crisis model. Fourth, it combines empirical analysis with forward-looking thinking, based on inputs from key policymakers and academics, in-depth real-world knowledge from practitioners, and seasoned judgment from IMF experts. The primary purpose of the EWE is to identify as early as possible the buildup of underlying vulnerabilities that predispose a system to a crisis, so that corrective policies can be implemented and contingency plans put in place.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet